MSME Development Based on Dynamic Capability Analysis and Upgrading Global Value Chain - Riyanto, Mohammad Aqil; Alfiansyah, Arya (Dinasti International Journal of Digital Business Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital sector proven to be resilient during economic crises, but now face significant challenges in the form of digital disruption and global competition. This study aims to analyze MSME development strategies in facing the digital economy era through the Dynamic Capabilities and Global Value Chain Enhancement approaches. The research method used is descriptive qualitative with a case study approach, utilizing observational data and a review of related literature. The research results show that to survive, MSMEs must possess dynamic capabilities that include adaptability, the ability to absorb new technologies, and innovative capabilities. Furthermore, MSMEs need to upgrade in the global value chain through three phases: improving technology-based production processes (process improvement), improving product concepts and philosophies (product improvement), and shifting functions to become active brand owners in digital marketing (functional improvement). In conclusion, the integration of e-commerce technology mastery, product innovation, and digital ecosystem support is crucial for MSMEs to increase competitiveness and national income.